Pengaruh Metode Nasakh Mansukh Terhadap Kedudukan Al-Qur’an Sebagai Mashadir Al-Ahkam - Muhamad Izazi Nurjaman (STIU Al-Mujtama Pamekasan, 2022)
This study presents a discussion of the influence of the Nasakh and Mansukh methods on the position of the Qur'an as mashadir al-Ahkam. Although there are differences of opinion among the scholars regarding the method of nasakh and mansukh in solving the problem of the two verses that seem to contradict. However, this method does not affect the position of the Al-Qur'an as mashadir al-Ahkam, but rather gives privileges to the position of the Al-Qur'an and provides its own features and challenges for the commentators to explore more deeply and broadly the legal provisions contained therein. Thus, of course it is obligatory for Muslims to stick to the Al-Qur'an as mashadir al-Ahkam in establishing a law. Keywords: Mashadir Al-Ahkam, Al-Qur'an and Nasakh Mansukh